Whole-Genome Sequencing of Neisseria gonorrhoeae Isolates with Antimicrobial Resistance Plasmids from a Homeless Community in Colombia (2022)
ABSTRACT: Neisseria gonorrhoeae is a pathogenic bacterium causing sexually transmitted infections, and it is associated with high antibiotic resistance rates. Here, we describe the genome sequences of four isolates from a homeless community in Colombia.